Building Innovation in Islamic Boarding School Learning through the Implementation of Educational Tools - Afiful Ikhwan (Yayasan Letiges Konsultan Sosial, 2025)
The phenomenon of stagnation in learning approaches in traditional Islamic boarding schools encourages the need for innovation to remain relevant in the digital era without abandoning the basic values of Islamic education. This study aims to examine the implementation of educational tools at the Darul Fikri Islamic Boarding School as part of learning innovation based on spiritual values and Islamic educational philosophy. This study uses a qualitative method with a case study approach through participatory observation and semi-structured interviews with female teachers and students. The results of the study show that traditional educational tools such as blackboards and yellow books still dominate in religious learning because they are considered effective in deepening understanding and fostering perseverance in learning. However, modern tools such as laptops and projectors are beginning to be used selectively for general subjects such as science and foreign languages to increase engagement and effectiveness in learning. Educators interpret these tools not as the main goal, but as a means or supporting means to help achieve the main values of Islamic boarding schools such as manners, closeness between teachers and students, and sincerity in learning. The conclusion of this study confirms that the integration of traditional and modern tools in Islamic boarding schools must remain based on Islamic spiritual and ethical values so as not to shift into secularization of education. The implication is that the wise use of educational tools can strengthen the quality of learning while maintaining the distinctive character of Islamic boarding schools. The limitations of this study lie in the scope that only covers one institution and has not compared similar implementations in other Islamic boarding schools. Therefore, further research is recommended to reach more institutions and evaluate the long-term impact of educational tool innovation on the formation of the character of students as a whole.